1981
DOI: 10.1203/00006450-198104001-00596
|View full text |Cite
|
Sign up to set email alerts
|

583 Continuous (C) vs. Intermittent (I) Nasogastric (N/G) Feeding in Very Low Birth Weight (Vlbw) Infants

Abstract: Previous studies have shown that Vitamin A levels are low in the growing premature infant. An attempt was made to raise Vitamin A levels by increasing oral intake in one of two groups of premature infants. Each group Jas 1 ma,ched for birth wt., gestational age 09set aqd voluie cc Kg/day) of feedings and caloric inta~e ~kcal/Kg/day. roup I infants were fed an ex-p~rimental formula prepared y Ros~ Laboratories of 500 IU Vit. A/dl while Group II receiv~d PM 60/40 (Ross) formula which contained 325 IU of Vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on the data of Krishnan et al, 3 we hypothesized that CNG feedings would result in a 35% decrease in the number of days required to reach full enteral feedings (primary outcome) as compared with IBG feedings. The sample size, based on an ␣ of .05 and a ␤ error of .20, was calculated to be 70 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the data of Krishnan et al, 3 we hypothesized that CNG feedings would result in a 35% decrease in the number of days required to reach full enteral feedings (primary outcome) as compared with IBG feedings. The sample size, based on an ␣ of .05 and a ␤ error of .20, was calculated to be 70 patients.…”
Section: Discussionmentioning
confidence: 99%
“…CNG methods have been recommended as a way of increasing energy efficiency because of improved absorptive capacity by the gut, 16,17 as a means of decreasing the amount of time required to reach full feedings 3,12 and as the best method for infants with intestinal disease. 18 Others have suggested that IBG may be more beneficial because of lower risk of precipitation into the delivery system or because of ease of administration because it does not require as much equipment; 4,5 however, this may be compensated by the nursing time required to deliver a bolus feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this feeding regimen may challenge the preterm infant's ability to maintain metabolic homeostasis and achieve growth. [2][3][4][5][6][7][8][9] Intrauterine growth restriction (IUGR) is a serious and common problem in obstetrics and in the NICU. 10 Placental dysfunction can impair fetal cardiovascular adaptation, characterized by a redistribution of cardiac output to maintain oxygen supply to the heart, adrenal glands, and brain at the expense of visceral organs (eg, the gastrointestinal tract).…”
mentioning
confidence: 99%